Hipertensi sebagai Prediktor Luaran Klinis pada Pasien COVID-19 pasien Rawat Inap: Studi di Rumah Sakit Achmad Mochtar - Najmi Hilaliyati; Reza Laila Najmi; Efilia Meirita; Izza Aulia Rizqika Nasution; Fitratul Wahyuni; Resi Rizki Banjarani (LPPM Universitas Abdurrab, 2025)
Populations with comorbidities, especially hypertension, are susceptible to COVID-19 infection and are known to be at risk of increasing disease severity, increasing the risk of poor clinical outcomes, and high mortality. There is no specific therapy to treat this disease, but several types of antivirals have been developed. The purpose of this study was to study the impact of comorbidities and antiviral therapy on clinical outcomes in the form of a length of stay and vital signs (pulse, respiratory rate, temperature, and oxygen saturation) of COVID-19 patients with or without comorbid hypertension. The study was conducted with a cross-sectional design. Data were collected retrospectively through the medical records of 80 patients who met the inclusion criteria and were treated during the period April 2020–March 2021 at Bukittinggi Hospital. Data were analyzed using the Mann-Whitney U Test, Kruskal Wallis Test, Friedman Test, and Repeated Measures Anova. The results showed that comorbidity had a significant impact on the patient's respiratory rate (p<0.05). The administration of different antivirals in patients with or without comorbid hypertension had a significant impact on the length of stay, body temperature, and oxygen saturation of patients (p<0.05). Patients receiving favipiravir therapy showed a shorter length of stay than the antivirals Oseltamivir, Ramdesivir and Hydroxychloroquine.